Early Serum Heme Oxygenase-1, Soluble Vascular Endothelial Growth Factor Receptor-1, and B-Cell Lymphoma/Leukemia-2 Levels and Unfavorable Obstetric Outcomes - Havva Sutcu; G. Fusun Varol; Cihan Inan; Isil Uzun; N.Cenk Sayin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To examine early pregnancy levels of serum heme oxygenase-1, soluble vascular endothelial growth factor receptor-1, B-cell lymphoma/leukemia-2 in relation to unfavorable pregnancy outcomes, including preeclampsia, fetal growth restriction, spontaneous preterm birth, gestational diabetes mellitus and fetal macrosomia.